The Age of synthesis : Vol. 3 : 1800-1895 - Spangenburg, Ray; Moser, Diane Kit (New Delhi : Viva Books, 2006)
Contributed papers presented at a seminar on the history of science and society in Indian context.
Includes bibliographical references.
Keywords: Science -- India -- History -- Congresses